A 12-yr profile of medical injury and illness for the Twin Cities Marathon - Roberts, W. O. (Medicine & Science in Sports & Exercise, 2000)
Objective: To summarize the medical encounters (injury/illness) for runners and the meteorologic data collected in the medical area of a large marathon race. Design: Prospectively transcribed medical records were analyzed for encounter rate, injury/illness type, treatment rendered, and outcomes. The environmental conditions for each race day are compared with injury/illness rates and types. Setting: An urban 42-km marathon located at 44°53`N latitude and 93°13`W longitude, scheduled on the first Sunday of October with an early morning start time. Participants: 81,277 entrants in the Twin Cities Marathon from 1982 to 1994. Main Results: The start temperature range was -4 to 16°C and the 4-h temperature range was 5-20°C. The average dew point was 3°C at the start and 4°C at 4 h. The finish area medical encounter rates for marathon runners were 18.9 per 1000 entrants and 25.3 per 1000 finishers. Mild injury/illness accounted for 90% of finish line medical encounters. Runners presented with exercise-associated collapse (59%), skin problems (21%), musculoskeletal problems (17%), and other medical problems (3%). Only 112 runners received intravenous fluids and 30 runners were transferred to emergency medical facilities. One death occurred in 1989. Conclusions: Marathon racing in cool conditions is a safe activity and most of the medical encounters are of minor severity. An early morning start time contributes to a cool racing environment and a low injury rate. More than 99.9% of runners who finish this race leave the finish area without hospital or emergency room care. The injury/illness profile can be used to tailor medical care at the finish area of marathons.